Rasionalitas Masyarakat Desa Suwaru Kecamatan Bandung Kabupaten Tulungagung dalam Melaksakan Yasinan Di Masa Pandemi Covid-19 - Erika Vivian Nurchahyati; Agus Mahfud Fauzi (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Abstrack The existence of the Covid-19 virus has made Indonesia impose large-scale social restrictions or PSBB. In this PSBB, restrictions are imposed, including on religious activities. Yasinan is a religious activity where people gather in one of the houses to read Yasin letters. This is of course contrary to the PSBB that is being enforced by the government. The purpose of this article is to find out the reasons for the community to carry out activities during the pandemic. This study used a qualitative research method with the research subjects of the Suwaru Village community. The data from this study were obtained through interviews. The theory used is Max Weber's concept of rationality. In the concept of rationality sees that there are actions from individuals that influence other individuals in determining a decision. The result of this research is that the community continues to implement yasinan because it has become a habit so it is difficult to get rid of it. Another thing that underlies them is by making sure the public believes that this can protect them from disasters such as the Covid-19 virus.